Representation of disabilities in Malaysian films: stereotypes, identities & the others - Yaakup, Hani Salwah (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2024)
Representation of the disabled community is often associated with negative stereotypes. This negative connotation, among others, includes the difficulty of having a perfect life, being considered a burden, not having opportunities for romantic relationships, and being dependent on others. In the Malaysian context, studies on the representation of disabilities through the media are still not extensive. The representation of these disabled is more prevalent on television programs. While in newspapers, the stereotype is maintained. At the same time, several locally produced films centered on this issue. Taking the problems mentioned as a basis, this study looks at the representation of the disabled in local films. This study uses a close reading method on 5 films which are Redha (Beautiful Pain) (2016), Pekak (2016), Guang (2018), MagiK (2023), and Abang Adik (2023). The findings reveal that while stereotypical representations persist, these films also highlight universal humanitarian issues and the talents and advantages of disabled characters. This new representation challenges existing stereotypes and offers a more nuanced view of disability. The study concludes that although there has been progress in portraying disabled characters in Malaysian films, further efforts are needed to ensure that media representations are inclusive and free from harmful stereotypes.